Validated UPLC-MS/MS method for the analysis of vitamin B6 pyridoxal 5́-phosphate, pyridoxal, pyridoxine, pyridoxamine, and pyridoxic acid in human cerebrospinal fluid - Rossmann, Julia; Christ, Stine; Richter, Sylvia; Garbade, Sven; Hoffmann, Georg F.; Opladen, Thomas; Okun, Jürgen G. (Journal of chromatography, 2022)
Vitamin B6 and its metabolites play a crucial role in the development and interaction of brain metabolism. Following diagnostic improvements additional inherited disorders in vitamin B6 metabolism have been identified, most of them leading to a severe epileptic disorder accompanied by progressive neurological deficits including intellectual disability and microcephaly. Since early treatment can improve the outcome, fast and reliable detection of metabolic biomarkers is important. Therefore, the analysis of vitamin B6 metabolites has become increasingly important, but is, however, still challenging and limited to a few specialized laboratories. Until today, vitamin B6 metabolites are measured by liquid chromatography tandem mass spectrometry (LC-MS/MS) using trichloroacetic acid for protein precipitation. In this work, we present the development and validation of a new, accurate and reliable method for analysis and quantification of the vitamin B6 vitamers pyridoxal 5́-phosphate (PLP), pyridoxal (PL), pyridoxine (PN), pyridoxamine (PM) and pyridoxic acid (PA) in human CSF samples using acetonitrile for protein precipitation.